Zika Virus: knowledge, feelings and social support network of pregnant women - Thiago Gomes de Oliveira; Elaine Lutz Martins; Alaidistania Aparecida Ferreira; Elijane de Fátima Redivo; Tarciso Feijó da Silva (Universidade Federal de Santa Maria, 2020)
Objective: to understand the knowledge, emotions and social support network of pregnant women with clinical suspicion or positive diagnosis of Zika virus. Method: a descriptive study with a qualitative approach, performed with ten pregnant women. Data were collected in the second semester of 2017, through semi-structured interviews and analyzed by thematic analysis technique. Results: the women demonstrated a lack of knowledge about the pathology and signs and symptoms during pregnancy. Feelings of fear, despair and tearfulness are associated with the possibility of fetal repercussions when faced with a diagnostic suspicion of microcephaly. Multiprofessional care, along with family and religious beliefs were seen to offer a support network for coping with the disease. Final considerations: knowledge, feelings and support networks are essential when considering the policies and organization of health services, from the perspective of coping and health care.